Better Health Systems for India's Poor : Findings, Analysis, and Options - Peters, David H.; Yazbeck, Abdo S.; Sharma, Rashmi R.; Ramana, G. N. V.; Pritchett, Lant H.; Wagstaff, Adam (Washington, DC: World Bank, 2013)
This report focuses on four areas of the health system in which reforms, and innovations would make the most difference to the future of the Indian health system: oversight, public health service delivery, ambulatory curative care, and inpatient care (together with health insurance). Part 1 of the report contains four chapters that discuss current conditions, and policy options. Part 2 presents the theory, and evidence to support the policy choices. The general reader may be most interested in the overview chapter, and in the highlights found at the beginning of each of the chapters in part 2. These highlights outline the empirical findings, and the main policy challenges discussed in the chapter. The report does not set out to prescribe detailed answers for India's future health system. It does however, have a goal: to support informed debate, and consensus building, and to help shape a health system that continually strives to be more effective, equitable, efficient, and accountable to the Indian people, and particularly to the poor.